2004
DOI: 10.3727/1525995042781011
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Behavioral Dependability of Sport Event Volunteers

Abstract: The dependability of volunteers in completing work assignments can impact upon the financial and operational success of major sport events and presents a significant challenge for event organizers. Despite the short-term nature of many events and the apparently manageable level of commitment, volunteers sometimes exhibit less than satisfactory levels of compliance to assigned tasks. Based on the theory of planned behavior (TPB), this study examined the behavioral dependability of operational-level volunteers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 41 publications
0
27
0
3
Order By: Relevance
“…Strigas and Jackson (2003) called for event volunteering motivational research to encompass different sport and recreation settings, different countries and cultures, and different types and scales of sporting events. There are a small number of studies that take a comparative or cross-case approach, comparing volunteering at different sporting events (Cuskelly, Auld, Harrington, & Coleman, 2004;Kemp, 2002), cultural festivals (Smith & Lockstone, 2009), or across a mix of event types (e.g., Monga, 2006). Treuren's (2014) study added to the multievent literature in surveying volunteers across five events.…”
Section: Lockstone-binney Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Strigas and Jackson (2003) called for event volunteering motivational research to encompass different sport and recreation settings, different countries and cultures, and different types and scales of sporting events. There are a small number of studies that take a comparative or cross-case approach, comparing volunteering at different sporting events (Cuskelly, Auld, Harrington, & Coleman, 2004;Kemp, 2002), cultural festivals (Smith & Lockstone, 2009), or across a mix of event types (e.g., Monga, 2006). Treuren's (2014) study added to the multievent literature in surveying volunteers across five events.…”
Section: Lockstone-binney Et Almentioning
confidence: 99%
“…These studies include comparing the motivations of event volunteers with their sociodemographic profiles (Kemp, 2002;Pauline & Pauline, 2009), the roles they undertake (Saleh & Wood, 1998), whether someone is a first time or repeat volunteer (Coyne & Coyne, 2001;Wollebaek, Skirstad, & Hanstad, 2014), and the training they receive (Costa, Chalip, Green, & Simes, 2006). Given the dependence of events on volunteers, a number of studies have also sought to identify whether volunteer motivation can predict volunteer retention (Coyne & Coyne, 2001;Cuskelly et al, 2004;MacLean & Hamm, 2007). Extending this work, surprisingly only recently have researchers (Alexander et al, 2015;Treuren, 2014) sought to cluster event volunteers into heterogeneous volunteer groupings, akin to events sampled in the current research include three hosted in Western Australia and one hosted in New Zealand.…”
Section: Volunteer Segmentationmentioning
confidence: 99%
“…Volunteers are essential for the sport industry as they enable event managers to maximize economic efficiency by minimizing staff costs, and contribute innovative ideas in their area of expertise (Cnaan & Goldberg-Glen, 1991;Cuskelly, Auld, Harrington, & Coleman, 2004;Shin & Kleiner, 2003). Prior research has indicated the value of volunteers, noting the critical role they play in the success of sportrelated organizations and sporting events (Cuskelly, 1998;Green & Chalip, 1998;Shilbury & Moore, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The literature on volunteering is relatively thin with regard to time-bound mega events, sporting and cultural, notwithstanding the contribution of, for example, Kemp (2002), Ralston et al (2003), Cuskelly et al (2004) and Green and Chalip (2004). What is evident is that without the volunteer contribution, most mega events would find it difficult to operate in either logistical/organisational or financial terms (Green and Chalip, 2004).…”
Section: Introductionmentioning
confidence: 99%